Characterization and suitability of polyphenols-based formulas to replace sulfur dioxide for storage of sparkling white wine. (February 2016) - Fracassetti, Daniela; Gabrielli, Mario; Costa, Carlos; Tomás-Barberán, Francisco A.; Tirelli, Antonio
Abstract: The sparkling wine protection against air is of interest for maintaining its sensorial profile and it is achieved through the use of antioxidants while disgorging. Sulfur dioxide (SO2 ) is commonly added, but its amount should be limited due to human health problems. The suitability of three polyphenols-based commercial formulas containing plant gallic and ellagic acids extracted from grape ( Vitis vinifera L.) (AO1), plant ellagic acid and gum arabic (AO2), and plant gallic, ellagic acids and Saccharomyces cerevisiae cell-wall fractions (AO3) was evaluated after 7 months storage (at 15 °C and 25 °C) of disgorged sparkling white wine. The phenolic composition of these formulas was investigated through spectrophotometric measurements. Moreover, the phenols were characterized and quantified by HPLC-MS analyses. The sotolon concentration and the absorbance values at 420 nm were determined in wines. The HPLC-MS analysis showed that the formula AO1 mainly contained gallotannins, ellagic tannins and flavan-3-ols, while AO2 had high levels of flavan-3-ols and gallotannins. Flavan-3-ols were the only phenols found in AO3. The addition of these formulas increased the yellow hue. Sotolon was higher than the perception threshold in the samples with AO2 and at trace amount in the samples with both AO1 and AO3 only stored at 25 °C. The tested antioxidant formulas seemed to be less effective of SO2 for the storage of sparkling white wine. However, the investigation of phenolics in antioxidant formulas could be helpful for the proper choice of a potential substitute of SO2 due to increase interest in sulfur-free wine production. Highlights: Addition of polyphenols formulas was investigated in sparkling white wine after disgorging. Certain markers of oxidation were evaluated in comparison to sulfur dioxide. The formulas seemed less protective against the oxidation than sulfur dioxide. The knowledge of the phenolics in the formulas allows their proper use in winemaking.